Five-year outcome of state-wide hip surveillance of children and adolescents with cerebral palsy - Kentish, M.; Wynter, M.; Snape, N.; Boyd, Roslyn (2011)
This study reports the five-year outcomes of a prospective population-based study of clinical hip surveillance for children with cerebral palsy (CP) according to evidence-based standards of care. Systematic hip surveillance commenced in Queensland, Australia as a state-wide program in 2005. Queensland represents a dispersed population across a large geographical area, creating unique challenges in terms of service delivery. Over five years, 1,115 children with CP were recruited, representing 73% of the expected population based on 1.9 to 2.1 per 1,000 live births. Standardized clinical and radiological assessments have been provided, with a median follow-up of 1.2 years (range 1 month- 5+8 yrs). Of the 1,115 children, 423 (38%) have been discharged and 692 (62%) remain on surveillance with 314 (28%) identified as having hip displacement with Migration Percentage (MP) equal to or greater than 30% (= 30). The incidence of marked hip displacement (MP = 30) was directly related to gross motor function, classified according to the gross motor function classification system (GMFCS), with distribution of GMFCS I=10, (3%), II=40 (13%), III=53 (43%), IV=96 (59%), and V=115 (64%). This state-wide surveillance program has been successful in correctly identifying children with hip displacement (MP = 30), fast tracking children for orthopedic review and discharging those at minimal risk. No child has progressed to dislocation while on surveillance without orthopedic review. © 2011-IOS Press and the authors. All rights reserved.